2018
DOI: 10.1016/j.biomaterials.2018.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Bioimaging predictors of rilpivirine biodistribution and antiretroviral activities

Abstract: Antiretroviral therapy (ART) has changed the outcome of human immunodeficiency virus type one (HIV-1) infection from certain death to a life free of disease co-morbidities. However, infected people must remain on life-long daily ART. ART reduces but fails to eliminate the viral reservoir. In order to improve upon current treatment regimens, our laboratory created long acting slow effective release (LASER) ART nanoformulated prodrugs from native medicines. LASER ART enables antiretroviral drugs (ARVs) to better… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 81 publications
1
41
0
Order By: Relevance
“…The sustained human grafts as confirmed by flow cytometry were viable and functional for more than 6 months, which provided a platform that allowed treatment interventions for prolonged time periods and a clear ability during ART to best establish a continuous latent HIV-1 reservoir in peripheral tissues and the brain and the noted immunological responses to the viral infection 12,17,29,36,37,39 . These previously published data support the successful use of humanized mice in studies of HIV/AIDS pathogenesis, therapeutics 40–42 , and treatment 1214,16,18,29,43,44 . These studies, taken together, clearly provide a rationale for the scientific approaches taken in the current report 12,13,29,43,45–47 .…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…The sustained human grafts as confirmed by flow cytometry were viable and functional for more than 6 months, which provided a platform that allowed treatment interventions for prolonged time periods and a clear ability during ART to best establish a continuous latent HIV-1 reservoir in peripheral tissues and the brain and the noted immunological responses to the viral infection 12,17,29,36,37,39 . These previously published data support the successful use of humanized mice in studies of HIV/AIDS pathogenesis, therapeutics 40–42 , and treatment 1214,16,18,29,43,44 . These studies, taken together, clearly provide a rationale for the scientific approaches taken in the current report 12,13,29,43,45–47 .…”
Section: Discussionsupporting
confidence: 68%
“…In earlier studies, we demonstrated editing of HIV-1 proviral DNA by CRISPR-Cas9 in in vitro and ex vivo T cells 18,22 . Here, we adapted a procedure as schematized in supplementary fig 1 and found that at sub-optimum conditions for CRISPR editing of viral DNA, suppression of viral replication by treatment of cells with ART enhances the efficiency of proviral DNA editing by CRISPR.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Hydrodynamic diameter and size of the nanocarriers were examined with Zetasizer Nano-S from Malvern Instruments. The stability of nanoparticles was examined as previously described [ 21 ]. The transmission electron microscopy (TEM) analysis was conducted as the following.…”
Section: Methodsmentioning
confidence: 99%
“…A sustained drug release and antiretroviral activity were observed in HIV infected macrophages. These multi-functional NPs represent a platform for the monitoring and optimization of the antiretroviral drug pharmacokinetic profile [170].…”
Section: Non-nucleoside Reverse Transcriptase Inhibitors Nanosystemsmentioning
confidence: 99%